2008
DOI: 10.1007/s10661-007-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contaminants in Canadian shorebirds

Abstract: Canadian shorebirds are exposed to environmental contaminants throughout their annual cycle. Contaminant exposure among species varies with diet, foraging behaviour and migration patterns. We sampled twelve species of shorebirds from four locations across Canada to assess their exposure to PCBs, organochlorine pesticides, as well as four trace elements (Hg, Se, Cd, As). SigmaPCB and SigmaDDT followed by SigmaCHL were most frequently found above trace level in the shorebird carcasses. In general, the plover spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Seabirds from other regions of the world showed a wide range of As levels (from 0.22 to 5.62 μgg −1 d.w. in liver; Lucia et al 2010;Ribeiro et al 2009) which could be related to differences in their diets (Kubota et al 2001). In accordance with Braune and Noble (2009), As levels in our samples were lower than 3 μg g −1 d.w. (see Table 3), which are usual levels in living organisms.…”
Section: Resultssupporting
confidence: 82%
“…Seabirds from other regions of the world showed a wide range of As levels (from 0.22 to 5.62 μgg −1 d.w. in liver; Lucia et al 2010;Ribeiro et al 2009) which could be related to differences in their diets (Kubota et al 2001). In accordance with Braune and Noble (2009), As levels in our samples were lower than 3 μg g −1 d.w. (see Table 3), which are usual levels in living organisms.…”
Section: Resultssupporting
confidence: 82%
“…The sample sizes in their study, however, ranged from 7 to 10. (Braune and Noble, 2009, dry weights) reported levels of mercury in liver of semipalmated sandpipers of 1.37 ppm in June in Churchill, and 1.23 ppm from Quill Lakes in August and 2.13 ppm in August/ September from the Bay of Fundy, supporting Didyk et al's suggestion of accumulating mercury while on migration. Hui et al (2001) reported levels in liver for several metals in western sandpipers (Calidris mauri) from San Francisco Bay: arsenic averaged 1.31-2.23 ppm (dry weight), cadmium averaged 1.06-1.23 ppm, chromium averaged 0.65 ppm, mercury averaged 4.43-4.17 ppm, and selenium averaged 12.2-13.4 ppm.…”
Section: Levels and Relationships Among Tissuesmentioning
confidence: 55%
“…Areas of Central and South America are of particular concern because mercury contamination is significantly increasing due to artisanal small-scale gold mining (UNEP 2013). Braune and Noble (2009) found liver mercury concentrations to be generally lower in 11 shorebird species sampled at noncontaminated sub-Arctic sites across Canada relative to those sampled in contaminated temperate wetlands . By contrast, however, Hargreaves et al (2010Hargreaves et al ( , 2011 found blood mercury concentrations in some shorebird species breeding in the eastern Canadian Arctic to be as high as those found in shorebirds sampled in mercury contaminated wetlands in San Francisco Bay.…”
Section: Introductionmentioning
confidence: 82%